PENGARUH PEMBERIAN DOSIS PUPUK NPK DAN PUPUK KANDANG AYAM TERHADAP PERTUMBUHAN DAN HASIL TANAMAN PARE (Momordica charantia L.) : Kata kunci: NPK, pupuk ayam, pertumbuhan, hasil, tanaman pare - Safitri Dwi Ningsih; Priyono Priyono; Saiful Bahri (Innofarm:Jurnal Inovasi Pertanian, 2023)
Research title "The Effect of Dosing of NPK Fertilizer and Chicken Manure on the Growth and Yield of Bitter Gourd (Momordica Charantia L.)". The research objective was to analyze the effect of chicken fertilizer and NPK fertilizer on the growth and yield of bitter gourd plants. This research was carried out from 8 August 2022 to 22 October 2022 at the Experimental Garden of the Faculty of Agriculture, Slamet Riyadi University, Surakarta, which is located on Jln. Jaya Wijaya No. 384 Kec. Banjarsari, Surakarta City, Central Java. The method used in this study was a Complete Randomized Design (CRD) consisting of 2 NPK factors (N) consisting of 4 levels, namely N0 (control), N1 (7 grams/polybag), N2 (14 grams/polybag), N3 ( 21 grams/polybag) and chicken manure (K) consisting of K0 (control), K1 (500 grams/polybag), K2 (1000 grams/polybag), K3 (1500 grams/polybag). Based on two factors, 16 combinations are obtained, each of which is repeated 3 times. Parameters observed were leaf color, flower appearance day, wet stover weight, dry stover weight, fruit length, fruit circumference, fruit weight, and number of fruit. The results showed that K2 at a dose of 1000 g/polybag and N3 at a dose of 21 g/polybag gave the best scores for the number of fruits, wet stover and dry stover. K2 dose of 1000 g/polybag and N2 dose of 14 g/polybag gave the best score on fruit length and fruit circumference. K3 dose of 1500 g/polybag and N2 dose of 14 g/polybag gave the best score on fruit weight. K3 dose of 1500 g/polybag and N3 dose of 21 g/polybag gave the best score on leaf color. K0 dose of 0 g/polybag and N3 dose of 21 g/polybag gave the best score on the day of flower appearance.